Fuzzy thinking : the new science of fuzzy logic - Kosko, Bart (Flamongo, 1994)
Fuzzy Thinking is the first popular book to explain clearly and provocatively how fuzzy logic is changing our lives - and how it will revolutionize the world in the decades ahead. Fuzzy thinking is the wave of the future, and the leading exponent of fuzzy logic, philosopher-scientist Dr. Bart Kosko, explains it better than anyone else can.